Perbandingan Penginputan Transaksi secara Manual Menggunakan Accurate pada Laporan Keuangan Input Transaksi Manual dengan Accurate di Laporan Keuangan - Meytha, Sri; Delfin. M, Vallen Ocshelyn (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This abstract discusses the comparison between manual transaction input and using Accurate in financial reports. Manual transaction input method involves the process of manually entering data into the accounting system, such as recording purchase transactions, sales, and other expenses. Although this method can produce accurate financial reports, it requires more time and effort from the inputting party. In addition, the risk of error is also higher because data entry is done manually. On the other hand, using Accurate as a transaction input system can improve the efficiency and accuracy of financial reports. Accurate is an accounting software designed to assist entrepreneurs or accountants in managing company financial transactions. By using Accurate, transaction input can be done automatically through integration with various data sources, such as cash register systems, purchase systems, and sales systems. This reduces the need for manual data entry, so the required time and effort can be minimized. In addition, Accurate also comes with automatic validation features that can reduce the risk of human error in inputting transactions. This feature will check the entered data and provide warnings or notifications if there are errors or non-compliance with applicable accounting rules. Thus, the accuracy of financial reports can be improved. In this study, a comparison will be made between manual transaction input and using Accurate in financial reports. By comparing these two methods, it is hoped that information can be found to help entrepreneurs or accountants in choosing the most efficient and accurate transaction input method for their company.